Towards a dual education system - a labour market perspective on poverty reduction in Bolivia - Jann Lay; Manfred Wiebelt (Kiel Institute of World Economics (IfW), 2001)
This paper addresses poverty reduction strategies from a labour market perspective. Structural features and constraints are emphasised using informality as a descriptive and segmentation as an analytical concept. Divergent demand-side developments combined with limited labour market mobility result in labour market segmentation. Vicious skill circles are identified that keep the poor trapped in jobs with low incomes. The analysis of the dimensions of informality in the Bolivian labour market shows that its characteristics do not correspond to the conventionally assumed informal-formal dichotomy. Empirical studies on the Bolivian case are reviewed that support the hypothesis of a segmented labour market with vicious poverty circles. The major policy conclusion for poverty reduction drawn from the analysis is that education should be more focused on employment.
Keywords: I3; R23; O17; 330; poverty reduction; Bolivia; dual education system; Dualer Arbeitsmarkt; Informeller Sektor; Armut; Armutspolitik; Bildungsreform; Duale Berufsausbildung; Bolivien